A photo zipper locked DNA nanomachine with an internal standard for precise miRNA imaging in living cells. Issue 24 (9th June 2020) - Zhang, Yue; Zhang, Yue; Zhang, Xiaobo; Li, Yuyi; He, Yuling; Liu, Ying; Ju, Huangxian
Abstract : A photo zipper locked DNA nanomachine with an internal standard is presented, preventing nonspecific activation and providing efficient intracellular miRNA imaging. Abstract : DNA nanomachines are capable of converting tiny triggers into autonomous accelerated cascade hybridization reactions and they have been used as a signal amplification strategy for intracellular imaging. However, the "always active" property of most DNA nanomachines with an "absolute intensity-dependent" signal acquisition mode results in "false positive signal amplification" by extracellular analytes and impairs detection accuracy. Here we design a photo zipper locked miRNA responsive DNA nanomachine (PZ-DNA nanomachine) based on upconversion nanoparticles (UCNPs) with a photo-cleavable DNA strand to block the miRNA recognition region, which provided sufficient protection to the DNA nanomachine against nonspecific extracellular activation and allowed satisfactory signal amplification for sensitive miRNA imaging after intracellular photoactivation. Multiple emissions from the UCNPs were also utilized as an internal standard to self-calibrate the intracellular miRNA responsive fluorescence signal. The presented PZ-DNA nanomachine demonstrated the sensitive imaging of intracellular miRNA from different cell lines, which resulted in good accordance with qRT-PCR measurements, providing a universal platform for precise imaging in living cells with high spatial–temporal specificity.